PENGARUH PROFESIONALISME PEMERIKSA PAJAK, KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN - Nur Cahyani; Ahyar Yuniawan (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2010)
This study aims to examine the effect of professionalism on the tax examiner jobsatisfaction and organizational commitment and its impact on improving employee performance.All the variables were based on the results of previous research, namely: Al-Meer (1989) and McNeese-Smith (1996), Shafer et al., (2001); Sagie and Krausz (2003); Lui et al., (2003) ; Cohenand Col, (2004) and Rizvi and Eliot (2005). Use of these variables can solve problems that occuron Regional Tax Office in Semarang, namely achievement of LPP settlement that does not reachthe target. Samples are tax inspectors in Semarang, some 171 tax inspectors. Structural EquationModeling (SEM), which is run by the AMOS software was used to analyze the data, the resultsshowed that the professionalism of the tax inspector has a positive and significant impact on jobsatisfaction, organizational commitment and employee performance. Job satisfaction has apositive and significant impact on employee performance and organizational commitment has apositive and significant impact on employee performance. The empirical findings indicate that toimprove employee performance in the tax office in Semarang area, need to pay attention tofactors such as tax inspectors professionalism, job satisfaction and organizational commitmentbecause of these factors proved to influence the level of employee performance.Keywords: professional tax inspectors, job satisfaction, organizational commitment, andemployee performance.